2015
DOI: 10.1513/annalsats.201410-461ar
|View full text |Cite
|
Sign up to set email alerts
|

Simulation for Skills-based Education in Pulmonary and Critical Care Medicine

Abstract: The clinical practice of pulmonary and critical care medicine requires procedural competence in many technical domains, including vascular access, airway management, basic and advanced bronchoscopy, pleural procedures, and critical care ultrasonography. Simulation provides opportunities for standardized training and assessment in procedures without placing patients at undue risk. A growing body of literature supports the use and effectiveness of low-fidelity and high-fidelity simulators for procedural training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 52 publications
0
28
0
Order By: Relevance
“…Therefore, even if trainees' performance improved over time, we are unable to address whether the benefit shown by the practice on the mannequin will translate into improved skills in vivo. Although previous studies reported a good correlation between skills gained in vitro and performance in vivo [4], the relationship between the use of our model and clinical performance will need to be evaluated in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, even if trainees' performance improved over time, we are unable to address whether the benefit shown by the practice on the mannequin will translate into improved skills in vivo. Although previous studies reported a good correlation between skills gained in vitro and performance in vivo [4], the relationship between the use of our model and clinical performance will need to be evaluated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, even low-fidelity simulators have proved to be effective, and in certain areas, such as basic bronchoscopy tasks, they may indeed be superior to high-fidelity computerized simulators [4].…”
mentioning
confidence: 99%
“…Supervised simulator-based training allows hospitalists to master basic components of a procedure 64 (including orientation to equipment, sequence of operations, dexterity, ultrasound anatomy, and real-time guidance technique) while improving both cognitive and manual skills. 42,43,[65][66][67][68][69][70][71] In addition to their role in basic training (which is outside the scope of this position statement), simulators can be useful for remedial training. To be sufficient for hospitalists who do not pass their patient-based assessments, however, remedial training that begins with simulation must also include patient-based training and assessment.…”
Section: If Remedial Training Is Needed Simulator-based Training Canmentioning
confidence: 99%
“…Flexible catheter (4) is used to connect 50 mL syringe with three-way stop-cock (5) and three-way stop-cock is used to change the channel of the withdrawn fluid e.g. to the 50-mL syringe and to the drainage bag (6). The drainage bag is used to collect the pleuritic fluid for further diagnostic examination.…”
Section: Image Processing Levelmentioning
confidence: 99%
“…The quality was also further enhanced with the recent advancements in surgical training regimes e.g. by employing surgical simulators [5] [6] in advanced surgeries, e.g. thoracic surgeries.…”
Section: Introductionmentioning
confidence: 99%